"If You Want to Know About the Book, Ask the Author": Enhancing Community Engagement Through Participatory Research in Clinical Mental Health Settings. Issue 2 (3rd April 2019) - Desai, Miraj U.; Bellamy, Chyrell; Guy, Kimberly; Costa, Mark; O'Connell, Maria J.; Davidson, Larry
Abstract: Participatory research, in which people with lived experience of the study phenomenon are involved as collaborators, has been conducted for decades; however, these innovations have struggled to take hold in mental health settings—until recently. The slow uptake of community partnered research in mental health has been unfortunate, especially because this field already suffers from poor community relations, pervasive community mistrust, and racial and ethnic disparities. But now, people with lived experience of severe mental illness—long considered to be "incapable" of functioning as co-researchers—are beginning to be included on research teams. However, training and opportunities for conducting such work are still lacking. This report describes a two-year initiative to improve the quality and quantity of participatory research being conducted in a department of psychiatry at a large medical school, which culminated in an innovative training program for both researchers and patients, developed in direct collaboration with stakeholders. In addition to detailing this program, we also discuss the deep legacy of mental health mistrust and our own efforts to address issues of social justice and health equity.